What You Don't Know CAN Hurt You—Or at Least Mislead You. - Behrman, Jere R. (Economia)
The text of the Carlos Diaz-Alejandro Prize Lecture is presented. The writer discusses human resources, household behavior, and social policies in Latin America. He recounts a number of key moments in his career as an empirical microeconomist involved in Latin America and the Caribbean before presenting a simple framework for analyzing household investments in human resources to illustrate why the unknown can be misleading in the presence of unobserved heterogeneities. The writer concludes by providing several related empirical illustrations based on his research in Latin America and the Caribbean and elsewhere.